Student spatial visual in geometry: the case of gender differences. Issue 1 (March 2021) - Yurmalia, D; Hasanah, A
Abstract: Spatial Visual, a mental representation in depicting visual information, is one of important ability in solving geometry problems. This study aimed to investigate student spatial visual ability and analyze it by gender. A total of participant involved in this research was 30 junior high school students at grade seven. There were three steps in this research. First, we chose two reflection questions from spatial visual assessment by Ramful, Lowrie, and Logan. Next, we interviewed some of students by semi structure interviewed. Finally, we analyzed student spatial visual comparing to types of visualization by Hegarty and Kozhevnicov and analyzed by gender. We found that generally the students had a lack in spatial visual ability because their pictorial representation, however boys had better spatial visual ability than girls.